The Influence of The Implementation of Elicit, Confront, Identify, Resolve, Reinforce (ECIRR) Learning Model on Learning Outcomes of Craft And Entrepreneurship (PKWU) By Controlling Learning Motivation - Ni Made Griantari; Ni Putu Sri Wati (International Journal of Multidisciplinary Sciences, 2023)
This research aimed to (1) describe the difference in PKWU learning outcomes results of grade XI Students of SMA NEGERI 1 Mengwi who studied using Elicit, Confront, Identify, Resolve, Reinforce (ECIRR) learning method and students who studied using the conventional method before and after students’ learning motivation variables were controlled and (2) describe the contribution on the learning outcome of students’ motivation variables on grade XI Students of SMA NEGERI 1 Mengwi who studied using Elicit, Confront, Identify, Resolve, Reinforce (ECIRR) and students who studied using conventional learning model. This research is experimental research (quasi-experimental) using a “post-test only control group) research design. The data were analyzed using one-way statistical analysis of variance (ANOVA) and one-way analysis of covariance (ANAKOVA) using F-test. The population of this research was all students of grade XI of SMA NEGERI 1 Mengwi with 15 study groups. The samples of this research were collected using sampling technique that was a random sampling technique. From 15 study groups, one group was taken as an experimental group (the group studied using Elicit, Confront, Identify, Resolve, Reinforce (ECIRR) learning model and another group was taken as a control group (the group studied using the conventional learning model). It was selected by lottery technique. The result of statistical analysis showed that (1) there was a difference in PKWU learning outcomes between students who studied using Elicit, Confront, Identify, Resolve, Reinforce (ECIRR) learning model and conventional model with Fcount= 17, 247 with significant (p)= 0,000 (p<0,05), (2). It also showed there was a difference in PKWU learning outcomes of students who studied using Elicit, Confront, Identify, Resolves, Reinforce (ECIRR) model and conventional model after the students’ learning motivation variables were controlled with Fcount = 27, 209; and (3) there was a positive and significant contribution between learning motivation and PKWU learning outcomes of 27, 04%. Based on the results, it can be concluded that Elicit, Confront, Identify, Resolve, Reinforce (ECIRR) learning model contributed to the PKWU learning outcomes before and after the students’ learning motivation variables were controlled.